Designing a Performance Evaluation and Payroll System Using the ADDIE Model - Rizky Kurnia Manggala; Riani, Lilia Pasca (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This research aims to design and develop an information system that integrates performance evaluation and payroll to enhance efficiency, transparency, and accuracy in human resource management. Design/Methode/Approach : This study uses the ADDIE model to design a performance evaluation and payroll system without full implementation. Research Finding : This research designs an integrated performance evaluation and payroll system to improve efficiency, transparency, and accuracy in HR management using the ADDIE model. Theoretical contribution/Originality : This research proposes a new conceptual model that integrates performance evaluation and payroll in one digital system, overcoming the limitations of previous studies with AI and data-driven approaches. Practitionel/Policy implication : This research is expected to create a more efficient, transparent, and data-based performance evaluation and payroll system to evaluate performance and improve compensation fairness. Research limitation : This research is only limited to discussing the evaluation and payroll system and only focuses on planning related to system creation.